Analyzing the Social and Cultural Determinants of Keeping and Using Firearms in Khuzestan Province - Masoumeh Bagheri; Marziyeh Shahryari; Sajad Bahmani; Ali Boduaghi (Strategic Research on Social Problems)
Introduction In many countries, including America, Canada, South Africa, Brazil, Colombia, and certain European nations, firearm-related injuries are a significant contributor to the overall number of deaths (Dahlberg, 2004). The majority of these incidents occur in countries where civilian firearm possession is unrestricted (Singh, 2005). According to a report from the United Nations, South Africa has the second highest rate of firearm-related deaths globally (Sanaei, 2004). In contrast, Iran has relatively few reported firearm injuries with the most recent official statistics from 2014 indicating over one million illegal firearms and a similar number of authorized firearms in circulation.